Single‐stage endoscopic treatment for mild to moderate acute cholangitis associated with choledocholithiasis: a multicenter, non‐randomized, open‐label and exploratory clinical trial. (25th November 2015) - Eto, Kazunori; Kawakami, Hiroshi; Haba, Shin; Yamato, Hiroaki; Okuda, Toshinori; Yane, Kei; Hayashi, Tsuyoshi; Ehira, Nobuyuki; Onodera, Manabu; Matsumoto, Ryusuke; Matsubara, Yu; Takagi, Tomofumi; et al.
Abstract: Background: Two‐stage treatment involving stone removal after drainage is recommended for mild to moderate acute cholangitis associated with choledocholithiasis. However, single‐stage treatment has some advantages. We aimed to assess the efficacy and safety of single‐stage endoscopic treatment for mild to moderate acute cholangitis associated with choledocholithiasis. Methods: A multicenter, non‐randomized, open‐label, exploratory clinical trial was performed in 12 institutions. A total of 50 patients with a naïve papilla and a body temperature ≥37 °C who were diagnosed with mild to moderate cholangitis associated with choledocholithiasis were enrolled between August 2012 and February 2014. Results: Of the 50 patients, 15 had mild cholangitis and 35 had moderate cholangitis. The median number of common bile duct stones was 2 (range, 1–8), and the median diameter of the common bile duct stones was 7.5 mm (range, 1–18). The cure rate of acute cholangitis within 4 days after single‐stage treatment was 90% (45/50) based on a body temperature <37 °C for ≥24 h. The incidence of complications was 10% (5/50). Conclusion: Single‐stage endoscopic treatment may be effective and safe for mild to moderate acute cholangitis associated with choledocholithiasis (clinical trial registration number: UMIN000008494). Abstract : Highlight Eto and colleagues demonstrated high cure rates and low complication rates in the first multicenter prospective study to verify the still controversial efficacy and safety of single‐stage endoscopic treatment involving endoscopic retrograde cholangiopancreatography and sphincterotomy for mild to moderate acute cholangitis associated with choledocholithiasis according to the TG07.